The Effect of Green Innovation, Environmental Performance, and Carbon Emission Disclosure on the Firm Value of Basic Materials Companies Listed on the Indonesia Stock Exchange for the 2021–2024 Period - Amsal Steven Trian Marpaung; Arthur Simanjuntak; Gracesiela Yosephine Simanjuntak; Merry Anna Napitupulu (Jurnal Ilmiah Accusi, 2026)
This research is conducted to investigate and evaluate the relationship between Green Innovation, Environmental Performance, and Carbon Emission Disclosure on Firm Value in companies operating within the Basic Materials sector listed on the Indonesia Stock Exchange during the 2021–2024 period. The study adopts a quantitative methodology and utilizes purposive sampling to obtain 39 firms that satisfy the predetermined research criteria. Informasi analysis is performed using IBM SPSS Statistics version 26, applying multiple linear regression to assess the interaction patterns among the examined variables. The empirical results indicate varying effects of the independent variables on Firm Value. Individually, Green Innovation shows a statistically significant positive effect on Firm Value among Basic Materials companies. In contrast, Environmental Performance presents a negative and statistically insignificant association with Firm Value. Similarly, Carbon Emission Disclosure demonstrates a negative but insignificant influence on Firm Value. However, when tested simultaneously, the three independent variables jointly exhibit a significant effect on Firm Value. Furthermore, the coefficient of determination analysis reveals that Green Innovation, Environmental Performance, and Carbon Emission Disclosure collectively account for 7. 3% of the variation in Firm Value, while the remaining 92. 7% is explained by other variables outside the research model. This study contributes to the literature by providing a broader understanding of how corporate environmental initiatives relate to firm value. The findings offer practical implications for investors and corporate management in formulating strategic and well- informed decisions. In addition, both theoretical and practical implications encourage further exploration of the role of Green Innovation, Environmental Performance, and Carbon Emission Disclosure in shaping Firm Value, particularly in the current masa where environmental sustainability has become a critical corporate responsibility